Drømme som almenpsykologisk fænomen - Hem, Lars (Psyke & Logos, 2015)
First, it is argued that the discovery of REM-sleep and its attributes disprove central elements in Freud’s arguments for the psychological meaningfulness of dreams. Next, Engelsted’s theory of REM-sleep as an important stepping-stone in the evolution of mammals is presented, and its implications for a theory of dreams is considered. Finally, Evan and Newton’s notion of dreams as a device to keep a biological information-processing system, the human brain, fully functional is described. In conclusion, Engelsted’s theory of REM-sleep and Evan and Newton’s theory of the cognitive function of dreams are considered to constitute a sufficient scientific foundation for most of the uses dreams are put to in modern psychotherapy.